RISK FACTORS OF HYPERTENSION IN THE ELDERLY - Debie Anggraini (Nusantara Hasana Journal, 2024)
Hypertension is caused by an abnormal increase in blood pressure beyond normal values, namely systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg measured at least twice in a sitting position. Hypertension indicates the occurrence of hemodynamic imbalance in the cardiovascular system caused by several aspects or multi-aspects and difficult to detect with one aspect only Methods: Hypertension detected during a physical examination is caused by certain diseases, so it is referred to as "The Silent Killer" because it often appears without symptoms. Elderly is someone who has entered the age of ≥60 years. Result: The elderly are at high risk of degenerative diseases, one of which is hypertension because the elderly will experience the aging process that causes changes in the body's work system such as cardiovascular. As we get older, the walls of blood vessels tend to be more rigid and their elasticity will decrease so that blood is forced to pass through narrow blood vessels and result in hypertension. Conclusion: Factors that often cause hypertension are divided into two factors such as gender, age, genetics and factors that can be changed such as diet, stress, obesity, physical activity, and smoking.